Debt Sustainability and Fiscal Resilience in the Era of Global Economic Uncertainty: JEL Classification: E62; F34; H63; H68; O23 - Nurul Aisyah Ramli; Ahmad Pratama Diantara (Generasi Sains Indonesia, 2026)
This study analyzes the relationship between debt sustainability and fiscal resilience in emerging economies during periods of global economic uncertainty. The research aims to examine how sovereign debt dynamics, fiscal imbalances, and macroeconomic instability influence governments’ capacity to maintain fiscal stability under external shocks. The study employs a quantitative panel data approach using observations from 25 emerging economies during the 2010–2025 period. Data were obtained from the International Monetary Fund, World Bank, OECD Statistics, and the World Uncertainty Database. The analysis applies Fixed Effects Model estimation, moderated regression analysis, and Generalized Method of Moments robustness testing. The findings indicate that public debt, fiscal deficits, external debt exposure, debt servicing obligations, inflation, and exchange rate volatility negatively affect fiscal resilience. In contrast, economic growth significantly strengthens governments’ fiscal adaptability and macroeconomic stability. The results also reveal that global economic uncertainty intensifies the adverse effects of debt accumulation on fiscal resilience. The study provides important implications for policymakers in designing adaptive fiscal strategies, strengthening debt governance, and enhancing economic resilience amid increasing global instability.